Language in multicultural education - Hoosain, R.; Salili, Farideh (Research in multicultural education and international perspectives., 2005)
Many books on multicultural education focus on a country and provide indepth discussion of issues pertinent to that country at the time. Alternately, understanding of multicultural education is sought through comparison between a society of special interest and a reference society, often the United States. An interesting recent example is Constructing Multicultural Education in a Diverse Society by Ilghiz Sinagatullin (2003), drawing on the author's knowledge of Russia and more particularly the Republic of Bashkortostan, itself an ethnically and culturally diverse part of Russia. The approach taken in this volume is to focus on an aspect of diversity, and look at its ramifications across the world. This provides an understanding of the nature of multicultural education itself, as well as insights into local issues through the experience of other places.